Validation of the General Decision Making in the Substance Use Instrument among Secondary School Students in Malaysia - Ahmad Jazimin Jusoh; Mohammad Khatim Hasan; Raja Jamilah Raja Yusof; Helmi Norman; Suzaily Wahab (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
The current research aimed to assess the validity of the decision-making process in the substance use instrument among secondary school students in Malaysia. This research used a survey research design. The current research participants were 211 secondary school students in Johor, Selangor, and Kedah, Malaysia. Two procedures were used to analyse the data: exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). EFA with comprehensive techniques that compromise parallel analysis and minimum average partial (MAP) yielded a 5-factor solution: avoidant decision making, rational decision making, spontaneous decision making, dependent decision making, and intuitive decision making. Furthermore, the factors attain a minimum standard of Communalities (.30 to 1.0) and factor loading (>.50). The structure of the instrument was then confirmed through Confirmatory factor analysis (CFA) with adequate fit indices such as RMSEA (<06 to .08), CFI, TLI (.80), and CMIN (<5). The instrument validation and reliability were tested through AVE, CR, and Cronbach's alpha.